공급 우선순위를 고려한 MODSIM과 K-WEAP 모형의 비교 및 고찰 - 오지환; 김연수; 류경식; 조영식; Oh, Ji-Hwan; Kim, Yeon-Su; Ryu, Kyong Sik; Jo, Young Sik (Journal of Korea Water Resources Association, 2019)
This study compared the characteristics of the optimization technique and the water supply and demand forecast using K-WEAP (Korea-Water Evaluation and Planning System) model and MODSIM (Modified SIMYLD) model considering wtaer supply priority. Currently, The national water resources plan applied same priority for municipal, industrial and agricultural demand. the K-WEAP model performs the ratio allocation to satisfy the maximum satisfaction rate, whereas the MODSIM model should be applied to the water supply priority of demands. As a result of applying the priority, water shortage decreased by an average of $1,035,000m^3$ than same prioritized results. It is due to the increase of the return flow rate as the distribution of Municipal and industrial water increases. Comparing the analysis results of K-WEAP and MODSIM applying the priorities, the relative error was within 5.3% and the coefficient of determination ($R^2$) was 0.9999. In addition, if both models provide reasonable water balance analysis results, K-WEAP is superior to GUI convenience for model construction and data processing. However, MODSIM is more effective in simulation time efficiency. It is expected that it will be able to carry out analysis according to various scenarios using the model. 본 연구에서는 공급 우선순위에 따른 물수급 분석 결과의 비교를 위해 국내 수자원장기종합계획에서 활용한 K-WEAP (Korea-Water Evaluation And Planing System) 모형과 MODSIM (Modified SIMYLD) 모형을 이용하여 분석하였다. 기존의 수자원장기종합계획은 수요처의 공급 우선순위를 모두 동일하게 공급하는 것으로 가정하여 분석하였으며 K-WEAP은 최대충족률을 만족시키기 위한 비율 배분을 수행하는 반면 MODSIM은 물 공급 우선순위의 적용이 필수적인 것으로 분석되었다. 먼저 우선순위에 따른 한강 유역의 물수급 분석 결과, 평균 1,035 천 $m^3$의 물부족이 감소하였으며 이는 생 공용수의 배분량이 증가하면서 회귀수량이 증가하고, 수자원의 재이용이 많아지기 때문인 것으로 분석되었다. 우선순위를 적용한 K-WEAP과 MODSIM의 분석결과를 비교할 경우, 상대오차 최대 5.3%이내, 결정계수($R^2$)는 0.9999로 매우 유사한 물 부족이 발생하였다. 또한 두 모형 모두 합리적인 물 부족 분석 결과를 제공한다면, 모형의 구축과 데이터 처리에 해당하는 GUI 편의성은 K-WEAP이 더 우수한 것으로 나타났으나, 구동시간의 효율성은 MODSIM이 더 우수한 것으로 분석되었다. 향후 K-WEAP모형 뿐만 아니라 MODSIM 모형을 활용한 다양한 시나리오에 따른 분석을 수행할 수 있을 것으로 기대된다.